Pengaruh Retailing Mix dan Kualitas Layanan terhadap Kepuasan Pelanggan dan Dampaknya pada Behavioral Intentions (Studi Kasus: "Hypermart" Malang Town Square, Malang) - By, Djasly (Jurnal Aplikasi Manajemen, 2008)
Customer buying behavior is affected by Environment changes. They like one stop shopping concept, because of its comfortable and variances of products, which are they shouldnt get some products in different places for each. With the amount of products and large area that hypermarket has, so it can be applied this one stop shopping concept. There's much competitors in hypermarket business, it needs the strategy to keep their old customers or get some new customers, and being focus on customer satisfaction for its effect on behavioral intentions in the future. Besides the service quality factor that can be affected to customer satisfaction in retail business, there is need to learn about retailing mix concept. Knowing the customer perceptions of retailing mix and service quality especially in "Hypermart" Malang Town Square (MATOS) and also knowing the retailing mir and service quality effect of customer satisfaction and behavioral intentions, are the aims of this research. Confirmatory analysis is including to the survey category of this research. Purposive sampling technique was used in this research with 148 respondents of it. The analysis of this research was using SEM (Structural Equation Modeling method with LISREL 8.30 program to make it work. Mostly, The customers value for their perception of retailing mix and service quality in "Hypermart MATOS" are good enough, like their strategist location, their variances of product, their high quality standard, their price of product that's similar to its quality, and their brands can be used optimally. Besides that, the high service quality in this "Hypermart MATOS" can make well customer satisfaction and also for the customer's behavioral intentions on the future.